2016
DOI: 10.1080/14789949.2016.1195005
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risks for male street gang affiliation: a systematic review and narrative synthesis

Abstract: Gang violence has increased in recent years. Individuals are becoming gang affiliated younger, and many have suffered historic maltreatment. Subsequent exposure to violence can result in profound consequences, including acute psychological harm. This review aims to identify predictive risk factors for male street gang affiliation. A systematic literature search was conducted utilising PsycINFO, PsycARTICLES, Medline, the Cochrane Central Register of Controlled Trials, the Cochrane Database of Systematic Review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 239 publications
2
35
0
Order By: Relevance
“…Results from the systemic review (Raby & Jones, 2016) and intelligence sources (Home Office, 2013;IGU, 2013), supported by previous research findings (Pyrooz, 2014), indicated a particular vulnerability to gang affiliation upon transition to secondary school. Therefore, our ultimate aim was to develop a self-report questionnaire that could be given to children around the age of 11 years that could predict their risk of subsequently becoming gang affiliated.…”
Section: Aimssupporting
confidence: 53%
See 4 more Smart Citations
“…Results from the systemic review (Raby & Jones, 2016) and intelligence sources (Home Office, 2013;IGU, 2013), supported by previous research findings (Pyrooz, 2014), indicated a particular vulnerability to gang affiliation upon transition to secondary school. Therefore, our ultimate aim was to develop a self-report questionnaire that could be given to children around the age of 11 years that could predict their risk of subsequently becoming gang affiliated.…”
Section: Aimssupporting
confidence: 53%
“…The first stage pertained to measure development and the creation of a pilot GARM (P-GARM) (see Appendix 1 in online materials). This included consultation with a range of experts to gain an improved understanding of whether risks identified in the systematic review (Raby & Jones, 2016) aligned with their operational or lived experience of gang affiliation in the UK. Thereafter, this stage involved a process of item design and selection for the P-GARM.…”
Section: Designmentioning
confidence: 99%
See 3 more Smart Citations